2023
DOI: 10.1097/sla.0000000000005908
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Effect of Liver Resection in Extended Cholecystectomy for T2 Gallbladder Cancer Revisited

Abstract: Objective: This study aimed to evaluate the effect of liver resection on the prognosis of T2 gallbladder cancer (GBC). Background: Although extended cholecystectomy [lymph node dissection (LND) + liver resection] is recommended for T2 GBC, recent studies have shown that liver resection does not improve survival outcomes relative to LND alone. Methods: Patients with pT2 GBC who underwent extended cholecystectomy as an initial procedure and did not reoperation after cholecystectomy at 3 tertiary referral hospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…A total of 26 studies 9 , 10 , 16 , 17 , 23 , 28 30 , 32 , 33 , 36 , 38 , 39 , 41 45 , 47 51 , 54 56 with 4603 cases were incorporated. Pooled results indicated that lymph node metastasis was a validating risk factor for OS (HR=2.78, 95% CI: 2.35–3.28, P <0.00001) (Figure S1F, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…A total of 26 studies 9 , 10 , 16 , 17 , 23 , 28 30 , 32 , 33 , 36 , 38 , 39 , 41 45 , 47 51 , 54 56 with 4603 cases were incorporated. Pooled results indicated that lymph node metastasis was a validating risk factor for OS (HR=2.78, 95% CI: 2.35–3.28, P <0.00001) (Figure S1F, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 8 studies 28 , 29 , 32 , 38 , 42 , 43 , 45 , 48 with 1615 cases were incorporated. Pooled results indicated that vascular invasion was a risk factor for OS among resected cases with GBC (HR=2.28, 95% CI: 1.87–2.79, P <0.00001) (Figure S1I, Supplemental Digital Content 4, http://links.lww.com/JS9/C302 ) (Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A multivariate analysis showed lymph node involvement and perineural invasion, but not the absence of liver resection, as risk factors for worse survival outcomes. The researchers recommended T2 stage extended cholecystectomy with lymphadenectomy, without hepatic segment IV and V resection in selected cases[ 101 ]. Perineural invasion has been considered an important indicator of early recurrence and worse prognosis.…”
Section: Managementmentioning
confidence: 99%